Kształtowanie się dochodów a poziom i struktura wydatków młodych małżeństw - Podolec, Barbara; Ulman, Paweł; Wałęga, Agnieszka (Income Versus Level and Structure of Young Couples Expenditure, 2007)
This paper is concerned with research on household budgets. Consumer needs of young people differentiate this group of households from the others. Different needs concern the process of organizing new independent life and setting up home. This article presents level and structure of young couple households expenses in context of their income. The authors take notice especially of expenditure combined with maintenance and equipment of apartment. The results of statistical analysis of young couple households budgets are presented in the context of demographic, socioeconomic and territorial characteristics
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 246-261